2016
DOI: 10.1186/s12883-016-0700-6
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine, an autophagy inhibitor, potentiates the radiosensitivity of glioma initiating cells by inhibiting autophagy and activating apoptosis

Abstract: BackgroundGlioblastoma is refractory to conventional treatment, which is combined of surgery, chemotherapy and radiotherapy. Recent studies have shown that glioma initiating cells (GICs) contribute to tumorigenesis and radioresistance. Recently, other studies showed that the GICs use the autophagy as the major pathway to survive. Chloroquine, an anti-malarial chemical, is an autophagic inhibitor which blocks autophagosome fusion with lysosome and slows down lysosomal acidification. The aim of this study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(67 citation statements)
references
References 31 publications
(27 reference statements)
3
64
0
Order By: Relevance
“…After the chloroquine treatment, the number of LC3 II puncta also increased by immunofluorescence. Some studies have shown that chloroquine could be a potential radiation sensitizer by inhibiting autophagy [21, 29]. In the current study, we explored the radiosensitizing effects of chloroquine in bladder cancer in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the chloroquine treatment, the number of LC3 II puncta also increased by immunofluorescence. Some studies have shown that chloroquine could be a potential radiation sensitizer by inhibiting autophagy [21, 29]. In the current study, we explored the radiosensitizing effects of chloroquine in bladder cancer in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Golden et al [23] suggested that chloroquine blocked autophagy and triggered endoplasmic reticulum stress, thereby increasing the chemosensitivity of glioma cells to temozolomide. In addition, Ye et al [21] showed that chloroquine enhanced the radiosensitivity of glioma initiating cells. It is therefore of interest to elucidate the association between chloroquine and radiosensitivity in bladder cancer.…”
Section: Introductionmentioning
confidence: 99%
“…This could account, in part, for a better drug delivery to solid tumors under KMT. The antimalarial drug, chloroquine neutralizes lysosomal pH reducing phagocytosis and autophagy, and thus depriving invasive and metastatic tumor cells from obtaining glucose and glutamine (34,204,205). Chloroquine can also inhibit mitochondrial diaphorases that oxidize NADPH to NAD+, which in turn would reduce mSLP (46,206).…”
Section: Ketogenic Metabolic Therapymentioning
confidence: 99%
“…In addition to its role in cellular homeostasis, autophagy also contributes to programmed cell death, 14 which can induced apoptosis via enhancing tumour necrosis factor-related apoptosis-inducing ligand (TRAIL). [16][17][18] Inhibition of autophagy activation is beneficial for BBB integrity in early stage in stroke. [16][17][18] Inhibition of autophagy activation is beneficial for BBB integrity in early stage in stroke.…”
Section: Introductionmentioning
confidence: 99%
“…15 A growing body of evidences indicate that autophagy is important for the functional recovery of several central nervous system (CNS) diseases. [16][17][18] Inhibition of autophagy activation is beneficial for BBB integrity in early stage in stroke. Enhanced autophagy by rapamycin (RAPA) further causes ZO-1 degradation and MMP-9 secretion after high glucose-induced damage.…”
Section: Introductionmentioning
confidence: 99%